FOREIGN EXPERIENCE OF TAX RATE REGULATION (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article describes the current state of regulation of tax rates for current taxes and ways of applying foreign experience to the tax system of Uzbekistan. Also, at the end of the work, proposals were formulated for the modernization of tax relations